2021
DOI: 10.21037/cdt-20-839
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic therapy in patients with atrial fibrillation undergoing percutaneous coronary intervention, including compliance with current guidelines—data from the POLish Atrial Fibrillation (POL-AF) Registry

Abstract: Background: Although triple antithrombotic therapy (TAT) is recommended in patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI), guidelines allow an option of dual antithrombotic therapy (DAT). This study assesses the everyday practice of 10 cardiology departments in antithrombotic therapy in AF patients undergoing PCI and its agreement with current guidelines.Methods: This analysis included medical data of AF patients enrolled in the prospective, observational registry (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Study designs included 14 retrospective record reviews [ 20 21 22 23 24 25 26 27 28 29 30 31 32 33 ], 6 cohort studies [ 34 35 36 37 38 39 ] and 1 a case-control [ 40 ] (see Table 1 ). Four studies focused on overuse, 5on underuse, and 12 on both.…”
Section: Resultsmentioning
confidence: 99%
“…Study designs included 14 retrospective record reviews [ 20 21 22 23 24 25 26 27 28 29 30 31 32 33 ], 6 cohort studies [ 34 35 36 37 38 39 ] and 1 a case-control [ 40 ] (see Table 1 ). Four studies focused on overuse, 5on underuse, and 12 on both.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis was carried out on a group of patients from the Polish Atrial Fibrillation (POL-AF) registry. The methodology has been previously described in detail [9,10]. The POL-AF registry is a prospective, observational, multicenter study.…”
Section: Patientsmentioning
confidence: 99%
“…Interestingly, in the presented study, AF type or impaired kidney function were not shown to be the predictors of OAC use in patients at low thromboembolic risk. It has been reported that the aforementioned factors increase the risk of thromboembolic complications in patients with AF or predispose them to thrombus formation in the left atrial appendage [8][9][10][11][12][13][14][15][16][17][18][19][20]. Study results connected with anticoagulant overtreatment of patients with AF prove that it is common and most likely stems from using OACs due to temporary indications to anticoagulant therapy and from the presence of thromboembolic risk factors not included in the CHA 2 DS 2 -VASc score.…”
Section: Discussionmentioning
confidence: 99%
“…The POL-AF Registry (NCT04419012) was a prospective, observational study enrolling AF patients hospitalized in 10 cardiology departments in Poland (eight of them were academic and two regional). Details on the study design have been reported elsewhere [9][10][11]. In brief, consecutive hospitalized patients were included in the study on the condition that they were at least 18 years of age and had AF history reported by electrocardiography or in their case record.…”
Section: Study Populationmentioning
confidence: 99%